IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN AL-QUR`AN HADIS MATERI ILMU TAJWID DI MTsN 2 PADANG - Derti, Seswi; Remiswal, Remiswal; Khadijah, Khadijah (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This study discusses the implementation of the Merdeka Curriculum in the subject of Al-Qur'an Hadis, especially in the material of tajweed science at MTsN 2 Padang. This research aim to analyze and describe the implementation of the merdeka curriculum in Al-qur’an hadith subjects tajwid science material at MTsN 2 Padang. The method used in this research is a qualitative method with adescriptive approach. Data collection techniques are through obsevation, interviews and documentation. The results showed that the implementation of Merdeka Curriculum in the Al-Qur'an Hadith subject at MTsN 2 Padang has been running in accordance with the provisions, although it still faces several obstacles : 1) Learning planning is carried out through analysis of Learning Outcomes (CP), formulation of Learning Objectives (TP), preparation of Learning Objective Flow (ATP), and development of teaching modules and assessments, 2) In the implementation of learning, teachers have used various methods according to the teaching material, but the differentiation approach has not been fully realised optimally, especially in the process and content aspects, 3) Learning assessment includes formative and summative assessments with a combination of oral and written tests.